Left lung and liver hydatid cyst: managed in single surgery - Anand, Krishnanand; Bansal, Vishal (International Surgery Journal, 2020)
A 35 years male presented with history of pain left chest wall associated with cough, fever and blood in sputum on and off, complaint of pain in abdomen which was dull aching gradually progressive in nature since, 2 months. Radiologically diagnosed to have huge hydatid cysts both in left lung and liver. It is unusual to find such large cysts at multiple sites and organs as in this case. There are reports in the literature of staged management as well as simultaneous management of lung and liver hydatid cysts. Though concomitant cysts in lung and liver may be treated comfortably by one stage surgery. Here both cysts were enucleated in the same sitting by a combined thoracic and abdominal approach (left thoracotomy followed by laparotomy through right subcoastal incision). The technique is safe and results were comparable to two stage surgery. Albendazole treatment in post-operative period helps to prevent recurrence. This report emphasizes that surgical intervention for hydatid cysts at multiple sites done in a single stage is safe, lessens the financial burden and hospital stay by avoiding multiple surgeries and anaesthesia.